Non-small cell lung cancer stage migration as a function of wait times from diagnostic imaging: A pooled analysis from five international centres. (May 2021) - Bissonnette, Jean-Pierre; Sun, Alexander; Grills, Inga S.; Almahariq, Muayad F.; Geiger, Geoffrey; Vogel, Wouter; Sonke, Jan-Jakob; Everitt, Sarah; Manus, Michael Mac
Highlights: Wait time is detrimental to lung cancer patients due to disease progression. Successive PET/CT scans can assess disease stage migration. Metastatic and nodal disease progression occur much sooner for adenocarcinoma or stage IIIB patients. Reducing wait times may have a positive impact on treatment outcome and survival. Abstract: Introduction: Patients with non-small cell lung cancer (NSCLC) can experience rapid disease progression between initial staging FDG-PET scans and commencement of curative-intent radiotherapy (RT). Previous studies that estimated stage migration rates by comparing staging PET/CT and treatment-planning PET/CT images were limited by small sample sizes. Methods: This multicenter, international study combined prospective data from five institutions for PET-staged patients with NSCLC who were intended to receive curative-intent RT. TNM status was compared for staging and RT planning scans and the probability of TNM status and overall stage migration was analyzed as a function of the interval between PET/CT scans. The impacts of N classification, overall stage, and pathology were also studied. Results: Pooled data from 181 patients were analyzed. The median interval between PET/CT scans was 42 days (range, 2–208). Upstaging occurred in 32 % of patients. The overall rate of stage migration was higher for patients presenting with initial stage IIIB/IIIC disease (p = 0.006) and patients with N2−3 nodal disease (p = 0.019). Upstaging to M1 disease was significantly associated with initial stage IIIB/IIIC disease (HR = 15.2) and adenocarcinoma (HR = 10) histology. Conclusion: Longer intervals between imaging and treatment in patients with NSCLC were associated with high rates disease progression with consequent risks of geographic miss in RT planning and futile treatment in patients with M1 disease. Patients with more extensive initial nodal involvement and those with adenocarcinoma had the highest rates of stage migration. Dedicated RT planning PET/CT imaging is recommended, especially if >3 weeks have elapsed after initial staging.